Answer:
-4 - 12x / -4×(1+3x)
Explanation:
-2+(-6)×2x-2
- multiplying an odd number of negative terms makes the product negative
(+(-6)= - ) -2-6×2x-2
- calculate the product
(6×2=12) - -2-12x-2
-calculate the difference
(-2-2=-4) - -4-12x
SOLUTION: -4-12x
/
-2+(-6)×2x-2
- calculate the difference
(-2-2) - -4+(-6)×2x
- factor out - 2×2 from the expression = -2×2(1+3x)
-multiply the numbers
(2×2=4) - -4×(1+3x)
SOLUTION: -4×(1+3x)
*both solutions are correct but i wasnt sure, which method you would rather use*